The Regulation of Lithium Plating Behavior by State of Stripping in Working Lithium Metal Anode - Xiao, Ye; Xu, Rui; Xu, Lei; Zhan, Ying‐Xin; Ding, Jun‐Fan; Zhang, Shuo; Li, Ze‐Heng; Yan, Chong; Huang, Jia‐Qi (Advanced energy materials, 2023)
The enthusiasm of reviving lithium metal anodes has motivated the battery community to pursue higher Li utilization. To this end, an exhaustively complete stripping pattern (C‐stripping) is conventionally adopted to obtain a higher apparent Coulombic efficiency (CE) in individual cycles while ignoring the effects of Li stripping state on subsequent Li plating behavior. In this contribution, a partial stripping (P‐stripping) protocol, in which a tiny amount of active Li is intentionally reserved, is validated as beneficial for an improved realistic Li reversibility. Compared to the C‐stripping protocol, the partially reserved active Li in P‐stripping mode serves critically as nucleation sites for following Li plating, which not only reduces the nucleation overpotential for flattened Li deposition morphology, but also favorably facilitates the re‐utilization of the original solid electrolyte interphase (SEI). This explains the lower growth rates of both “dead Li” and SEI‐Li+ under the P‐stripping protocol. Benefitting from the intrinsically more reversible Li cycling, the anode‐free Cu||LiNi0.5Co0.2Mn0.3O2 cells using the P‐stripping protocol acquire higher available capacities in long‐term cycles. This work uncovers the crucial significance of the former state of Li stripping on regulating the following Li plating manner and SEI re‐utilization, providing fresh design implications toward more sustainable cycling of Li anodes. This work reveals the crucial significance of former Li stripping states on subsequent Li plating/stripping behavior for practical Li utilization. The partially reserved active Li not only lowers the nucleation overpotential for flat Li deposition morphology, but also favorably facilitates the re‐filling of Li into original solid electrolyte interphase (SEI) shells to minimize SEI reconstruction.